DIGITAL TRANSFORMATION AND EMPLOYEE ADAPTABILITY: A STUDY OF PSYCHOLOGICAL FACTORS INFLUENCING WORKPLACE INNOVATION - Dodi Setiawan; James Smith; Jack Davis (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Digital transformation has become a critical factor for organizational success, yet the ability of employees to adapt to technological changes remains a significant challenge. Employee adaptability is influenced by various psychological factors, which have not been sufficiently explored in the context of digital transformation. This study aims to investigate the role of emotional intelligence, cognitive flexibility, self-efficacy, and stress management in shaping employee adaptability during digital transformation processes. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with 300 employees and 30 managers from various industries undergoing digital transformation. Descriptive and inferential statistical analysis revealed that emotional intelligence, cognitive flexibility, and self-efficacy significantly correlate with employee adaptability, while stress management showed a weaker relationship. Qualitative interviews supported these findings, highlighting the importance of emotional intelligence in reducing resistance to change and fostering collaboration. The study concludes that organizations should prioritize developing these psychological traits to enhance employee adaptability and improve the success of digital transformation initiatives. The findings contribute to a deeper understanding of the psychological mechanisms involved in employee adaptation, offering practical implications for organizations aiming to optimize workforce performance during technological transitions.